Evaluation of the amount of nanoparticles emitted in LASER additive manufacture/welding - Gomes, J. F. (2019)
EU Project CERASAFE ERANET SIINN/0002/2014. CERENA strategic project (FCT-UID/ECI/ 04028/2019).